Nigeria : Financial Sector Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2013)
This Financial Sector Stability Assessment on Nigeria discusses the macroeconomic performance and structure of the financial system. Although Nigerian economy experienced both domestic and external shocks in recent years, the economy continued to grow rapidly, achieving more than 7 percent growth each year since 2009. The performance of financial institutions has begun to improve, though some of the emergency anti-crisis measures continue to be in place. However, the regulatory and supervisory framework has gaps and weaknesses. In sum, the Nigerian economy has emerged from the banking crisis, and has the potential to enjoy an extended period of strong economic growth.